Evaluation of Safety, Tolerability and Efficacy in Treating Chronic Constipation. Global Healing Center- Oxy Powder® in Treating Constipation and IBS. Clinical Trial Phase III - Jogender K. Lalla,; Meena U.Shah,; Edward III Group, (International Journal of Pharma and Bio Sciences, 2010)
To conduct a clinical trial for evaluating safety, tolerability and effectiveness of Oxy Powder® (OP) in patients of chronic constipation and Constipation – Predominant IBS. Constipation is the slow movement of feces through the large intestine resulting in the passage of dry, hard stools. Fecal impaction is a collection of dry, hard stool in the colon or rectum. Study Design: 6 weeks open, comparative, randomized study enrolling 40 patients of constipation and 20 of IBS. Trial Formulations: (A) Oxy powder ® (Marketed by Global Healing Center, Inc., USA) - Test Product A. (B) Dulcolax Tablets (DX), [manufactured by Zydus Cadila Ltd, (India)] - Reference Product B. Guidelines followed: (a) Rome criteria (b) GCP described under ICH E6 document (c) World Medical Association’s (WMA) Bioethics Declaration of Helsinki. (d) Schedule Y in Drugs and Cosmetic Act and (2nd Amendment) Rules, 2005, Ministry of Health and Family Welfare, Government of India, End Point(s): 1) Recording change in weight 2) The effectiveness of the product for Oxygen delivery in patients 3) Finding of (i) stool examination (ii) Barium Meal X-ray and (iii) Colonoscopy 4) Relief of constipation and IBS. Results and Discussion: There were insignificant changes in weight and blood oxygen levels during treatment in both the Groups. Stool examination did not show abnormality in any patient. Patients in both Groups showed significant reduction in various symptoms including a) straining, (b) passing of lumpy stools(c) sensation of incomplete evacuation & Anorectal Blockage and (e) manual maneuvers to facilitate Bowel movements. Overall Efficacy: In Group A, (out of 26), 11 (42.3%) had complete cure, 15 (57.7%) showed Improvement, In Group B, (out of13), 1 (7.7%) had complete cure,10 (76.9%) showed Improvement with 2 (15.9%) failures. Conclusion: Safety, Efficacy and tolerability of OP in treating constipation was significantly (P<.05) higher than DX